DESIGNING THE SUSTAINABILITY REPORTING MODEL FOR VILLAGE-OWNED ENTERPRISE BASED ON TRI HITA KARANA : A CONCEPTUAL APPROACH - Putu Sukma Kurniawan; Tjiptohadi Sawarjuwono (Universitas Airlangga, 2022)
This conceptual article aims to provide a new perspective on the possibility of implementing the concept ofsustainability in small business organizations. This conceptual article focuses on developing a sustainabilityreporting model for village-owned enterprise (VOE). The novelty shown in this conceptual article is the use oflocal Balinese wisdom, namely the Tri Hita Karana concept in helping to develop a sustainability reportingmodel for village-owned enterprise. The method of writing this conceptual article uses library research byfocusing on relevant documents and literatures. The results and discussions have been compiled to produce asustainability reporting model for village-owned enterprise. Future research can continue this conceptual articleby trying to implement the sustainability reporting model in village-owned enterprise.